2023
DOI: 10.1177/27324745221144308
|View full text |Cite
|
Sign up to set email alerts
|

Dispelling Myths Surrounding AAC Use for Children: Recommendations for Professionals

Abstract: Augmentative and alternative communication (AAC) includes methods and technologies to support communication and aid individuals with limited speech. There are many widespread misconceptions about AAC use, however, that can negatively impact how children with disabilities are taught in classrooms. In this article, we describe the main types of AAC systems and how they are used to promote child success. Then, we identify and dispel common myths about AAC use and provide evidence-based recommendations for practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Our second theme was on Stakeholder Attitudes and Stigma. As with past studies (4,9,13,16,20,22,24,27,34,35,(46)(47)(48)(49)(50)(51)(52), our parent-carers initially worried that their children will lose their potential for speech if they rely on AAC devices to 'speak for them', or that AAC devices will single their child out to peers as being different. The former is linked to stakeholder attitudes (i.e., belief in myths; 53), and the latter to stigma.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our second theme was on Stakeholder Attitudes and Stigma. As with past studies (4,9,13,16,20,22,24,27,34,35,(46)(47)(48)(49)(50)(51)(52), our parent-carers initially worried that their children will lose their potential for speech if they rely on AAC devices to 'speak for them', or that AAC devices will single their child out to peers as being different. The former is linked to stakeholder attitudes (i.e., belief in myths; 53), and the latter to stigma.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, clinicians who work with younger children or children with mainstream devices (e.g., ipads) may have more positive experiences. Societal stigma may be reduced by improving AAC interventions through peer-mediated interventions with explicit teaching of AAC use and turn-taking in children ( 49 , 54 ). When neurotypical peers were taught AAC interaction strategies, students using AAC enjoyed their interactions, saw their peers as friends, and were more involved in class activities ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…With support and opportunity, learners like Raúl can access the content of texts, communicate their emotions while reading, and seek to share their experience with communication partners (Han et al, 2021). Peer-supported learning has been shown to improve engagement (Shurr & Kromer, 2018) and improve the quality of social interactions for students who use AAC (Jensen et al, 2023). Through his connection to a culturally relevant text, Raúl's translanguaging is a bid to connect with a peer who shares his identity as an ML.…”
Section: Step 4: Creating Opportunities For Discussionmentioning
confidence: 99%
“…Many providers and educators hold overlapping misconceptions about the influence of multilingualism and AAC on language development for students with disabilities (Drysdale et al, 2015; Rizzuto, 2017). These misconceptions include beliefs that AAC support and multilingualism (a) can delay developing language skills (Soto & Yu, 2014) and (b) are too challenging for students with significant support needs (Jensen et al, 2023). However, existing research has shown that AAC and exposure to multiple languages each support the development of language, literacy, and social communication skills (Jensen et al, 2023; Kleekamp, 2021; Soto & Yu, 2014).…”
Section: Mls Who Use Aacmentioning
confidence: 99%
See 1 more Smart Citation